2019
DOI: 10.1115/1.4043038
|View full text |Cite
|
Sign up to set email alerts
|

Relative Motion Between the Helmet and the Head in Football Impact Test

Abstract: Approximately 1.6–3.8 million sports-related traumatic brain injuries occur each year in the U.S. Researchers track the head motion using a variety of techniques to study the head injury biomechanics. To understand how helmets provide head protection, quantification of the relative motion between the head and the helmet is necessary. The purpose of this study was to compare helmet and head kinematics and quantify the relative motion of helmet with respect to head during experimental representations of on-field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Previous research examining impact conditions using dummies had demonstrated noticeable differences between helmet and head kinematics which indicates that helmet motion does not necessarily correlate with head motion. 22 While lowering the trigger threshold may help to improve sensor recall at lower severity, the trade-off is potentially filling the sensor memory with spurious events that may limit recording of head impacts of all severities later in the game. Beyond adjustments to the triggering threshold, future system improvements could include increasing memory capacity to reduce the risk of filling memory while improving recall.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research examining impact conditions using dummies had demonstrated noticeable differences between helmet and head kinematics which indicates that helmet motion does not necessarily correlate with head motion. 22 While lowering the trigger threshold may help to improve sensor recall at lower severity, the trade-off is potentially filling the sensor memory with spurious events that may limit recording of head impacts of all severities later in the game. Beyond adjustments to the triggering threshold, future system improvements could include increasing memory capacity to reduce the risk of filling memory while improving recall.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in measurement methods and scientific rigour makes the derivation of severity metrics unreliable. For example, inertial measurement unit (IMU) sensors mounted externally to the head, either on the skin or in helmets and headbands, significantly overestimate peak linear acceleration (PLA) and peak rotational acceleration (PRA) (Joodaki et al, 2019;Patton et al, 2020b;Wu et al, 2016). This is due primarily to poor sensorskull coupling and soft tissue artefact (STA), where the skin deforms relative to the underlying bone (De Rosario, Page, Besa, Mata, & Conejero, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, a more extensive search for web videos could facilitate the application of the methods presented for other sports. Other biomechanical studies have been considered by tracking in alternative sports, such as American football [35], rugby [39], baseball [6], basketball [33], Gaelic field [37], snowboard [41], skiing [40], among others. However, such mentioned studies are limited to the analysis of the efforts generated on sensors when stepping or making direct contact, or by consensus decision by experts in the area in case.…”
Section: Discussionmentioning
confidence: 99%